Ezekiel and the world of Deuteronomy - Gile, Jason (London Bloomsbury Publishing Plc, 2021)
Cover -- Title -- Copyright -- Contents -- Acknowledgments -- List of Abbreviations -- Chapter 1 Introduction -- Ezekiel's Use of Texts and Traditions -- Citing Scripture in an Oral World -- Ezekiel's Relationship to Deuteronomy -- The Terms "Deuteronomic" and "Deuteronomistic" -- The Status of Deuteronomy at the Time of Ezekiel -- Scholarly Views on Ezekiel and Deuteronomy -- Ezekiel the Prophet, Ezekiel the Book -- The Unity of the Book -- Ezekiel's Role in Producing the Book -- A Widespread Deuteronomistic Redaction of Ezekiel? -- The Septuagint and Scribal Expansion -- Preview of This Study -- Chapter 2 Method for Assessing Influence -- Recognizing Influence -- Explaining Verbal Parallels -- Defining Deuteronomic Influence -- Identifying Literary Dependence -- The Significance for Interpreting the Book of Ezekiel -- Chapter 3 Idolatry -- The Basis for Ezekiel's Indictment against Idolatry -- Ezekiel and the Pentateuchal Descriptions of Idolatry -- Deuteronomic Language for Idolatry in Ezekiel -- שקוצים , "Detestable Things" -- תועבות , "Abominations" -- העביר בנים באש , "Passing Children through the Fire" -- הכעיס , "Provoke to Anger" -- הלך אחרי אלהים / גלולים"Going after Gods / Idols" -- עיניו נשא , "Lifting One's Eyes (to "(גלולים -- "Divination" -- Worshiping Idols in Exile -- Non-Centralized Worship -- "On Every High Hill, Under Every Leafy Tree" -- על ההרים אכל , "Eating on the Mountains" -- דע , "Cut Down" -- נתץ , "Tear Down" -- Centralized Worship in the Renewed Jerusalem -- Ezekiel's Temple Vision (Chapter 8) -- Scene 1: The Image of Jealousy (8:5-6) -- Scene 2: The Elders and Their Images (8:7-13) -- Excursus: A Marzea? in Ezekiel 8:7-13? -- Scene 3: The Women Weeping "the Tammuz" (8:14-15) -- Scene 4: Astral Worship (8:16-18) -- Ezekiel's Vision and Manasseh's Sins -- Ezekiel and Deuteronomy 4 -- Literary Links.
Description based on publisher supplied metadata and other sources
Keywords: Ezekiel-(Biblical prophet); Bible-Criticism, interpretation, etc; Bible.-Deuteronomy-Influence; Influence (Literary, artistic, etc.); Electronic books